1990
DOI: 10.1016/0360-5442(90)90016-u
|View full text |Cite
|
Sign up to set email alerts
|

6.2. Tools for energy planning in developing countries

Abstract: -This paper analyzes the different methods available today for treating major issues in developing countries. The authors discuss problems which have already been addressed by existing models and those that need to be solved. INTRODUcnONThe energy situation in developing countries is getting more and more complex. While in the industrialized countries a more or less stable level of the energy demand has been reached, developing countries still face twindling growth rates for both, commercial and traditional fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 2 publications
0
1
0
Order By: Relevance
“…The most relevant tools for energy planning are models which mathematically represent a simplification of reality [6]. The tool for this study is the BIOFUEL model as shown in Figure 2.…”
Section: Model Descriptionmentioning
confidence: 99%
“…The most relevant tools for energy planning are models which mathematically represent a simplification of reality [6]. The tool for this study is the BIOFUEL model as shown in Figure 2.…”
Section: Model Descriptionmentioning
confidence: 99%